A PRÁTICA PEDAGÓGICA NO PROCESSO DE ALFABETIZAÇÃO E LETRAMENTO NO ENSINO REGULAR E MULTISSERIADO - Joyce Formiga Moura, Ralydiana (Humanas em Perspectiva, 2021)
This study addresses the issue of literacy and literacy in the early years of elementary school, considering the classes with regular and multi-grade education, starting from an analysis of pedagogical practices developed in the classroom, with relevant aspects such as: initial education and continuing of teachers, relating to the practices carried out in the school environment and at work with literacy and literacy. The objective was to analyze which factors influence the development of pedagogical practices from the perspective of literacy and literacy in the early years of elementary school in regular and multi-grade classes in the city of Pombal-PB. The methodology used starts from a descriptive study with qualitative and quantitative approach, characterized as a field research and having as research instruments structured questionnaires with open and closed questions, in an attempt to get as close to the reality of the object of study as possible analysis and reflection of the collected data and the contribution of some authors on the aborted theme. It was found with field research that several factors influence the development of pedagogical practice, such as: lack of teacher training programs that contribute to the relationship between theory and practice, more effective family participation in school and organization of teaching. meet the needs of the teaching and learning process with smaller classes not organized in multi-grade education. It is hoped that the present study can contribute to important discussions about pedagogical practices focused on the teacher’s work and the process of literacy and literacy, with influence on the academic environments, the pedagogical practice of teachers and the different contexts that involve actions turned on the teaching and learning process.